A multi-criteria decision (fuzzy) approach for IoT adoption in developing nation: a study during COVID-19. (27th April 2023) - Rastogi, Sanjay
The wave of IT development and adoption has changed the global scenarios. In this race, emerging economies are also competing with the developed economies. Internet of things (IoT) is now touching everyone's life. Irrespective of this growth and benefits, people from developing nations are still in fix to adopt life changing technology. This study was conducted in COVID-19 times when people were in lockdown and were becoming more dependent on technology. This study tries to understand the factors leading to adoption IoT in emerging economies. A fuzzy-MCD approach was used to rank the factors resulting from CFA. Results advocated the importance of facilitating conditions to promote the usage and acceptance of technological change followed by IT expertise and social influence. Findings provided practical reference for authorities and policy makers involved in designing strategies for technology implementations and promotions.